Centromere formation in mouse cells cotransformed with human DNA and a dominant marker gene. - Hadlaczky, G (1991)
A 13,863-base-pair (bp) putative centromeric DNA fragment has been isolated from a human genomic library by using a probe obtained from metaphase chromosomes of human colon carcinoma cells. The abundance of this DNA was estimated to be 16-32 copies per genome. Cotransfection of mouse cells with this sequence and a selectable marker gene (aminoglycoside 3'-phosphotransferase type II, APH-II) resulted in a transformed cell line carrying an additional centromere in a dicentric chromosome. This centromere was capable of binding an anti-centromere antibody. In situ hybridization demonstrated that the human DNA sequence as well as the APH-II gene and vector DNA sequences were located only in the additional centromere of the dicentric chromosome. The extra centromere separated from the dicentric chromosome, forming a stable minichromosome. This functional centromere linked to a dominant selectable marker may be a step toward the construction of an artificial mammalian chromosome.